The Functional Convergence of Wasiat, Hibah, and Wasiat Wajibah: Reconstructing Indonesian Islamic Inheritance Law through a Graduated Configuration Model - Nihayatun Nisa'; Sri Hafsari Fakriyah; Sesarian Nur Khoiriyah Sukarno; Fadhila Assabili (NALAR FIQH: Jurnal Hukum Islam, 2025)
The Islamic inheritance system in Indonesia comprises three doctrinally distinct instruments of asset distribution: wills (wasiyyah), gifts (hibah), and mandatory bequests (wasiat wajibah). In contemporary legal practice, these instruments increasingly overlap in function. While existing literature generally examines them separately, this study addresses that gap through normative legal research (doctrinal legal research), employing conceptual, statutory, case law, historical, and comparative approaches to examine how the legal boundaries of one instrument shape the function of the others. The analysis draws on primary legal materials, including the Compilation of Islamic Law (KHI), particularly Articles 171(c), 195-214, and 209, Supreme Court Decisions No. 51 K/AG/1999 and No. 16 K/AG/2010, as well as classical fiqh and Maqasid al-Shariah literature. The findings demonstrate that wills, gifts, and mandatory bequests no longer operate as ontologically separate categories but instead constitute an interdependent continuum of asset distribution shaped by the mechanisms of talfiq and takhayyur within the KHI. The one-third limitation and heir consent requirements governing wills have encouraged a functional shift toward gifts, while judicial expansion of mandatory bequests to non-Muslim heirs reveals an unresolved tension with Article 171(c), which requires heirs to be Muslim. To explain this legal configuration, the study proposes the Graduated Configuration Model, consisting of the source of obligation test, the shared cap principle, and the substance over form test, evaluated through an integrated framework of Maqasid al-Shariah, legal pluralism, and siyasah shar'iyyah. This model offers a novel theoretical framework for understanding Indonesian Islamic inheritance law as a unified and functionally interconnected system rather than as three separate legal instruments.